Konsep dan Rancangan Pembangunan "Kampung Beasiswa" Pemerintah Provinsi Sumatera Utara - Dr. Ir. Hj. Sabrina, M. Si Sabrina Sabrina (Inovasi, 2021)
Education is an important element in the quality of human resources, so that it is necessary to increase the degree of community education. The North Sumatra Province RPJMD 2019-2023 contains Dignity in Education as a mission, and one of its development priorities is the Improvement and Fulfillment of Access to Education. The Government of North Sumatra plans that the community can receive education up to the level of higher education. The Gross Enrollment Rate (APK) and Net Enrollment Rate (APM) of Higher Education in North Sumatra are relatively low. The APK and APM of Higher Education in North Sumatra in 2020 are 25.76 and 22.20, respectively. This is also related to the dropout rate, especially at the high school level (SMA and SMK). The dropout rate for North Sumatra in 2020 for the SMA level is 0.43 and the SMK is 1.10. As a qualitative research,the data used were both secondary and primary data. Primary data were collected through questionnaires and limited interviews with randomly selected respondents from students, parents, teachers and the general public. Secondary data were collected from documents, reports, releases/books and other references from various sources or agencies. The data were analyzed descriptively to obtain an overview of the existing conditions and problems to underlie the preparation of the concept and design of the “Scholarship Village”. In this study, it was found that people who dropped out of school were generally due to their inability to pay tuition fees and lack of information about scholarships, the latter regarding the sources of scholarships and how to access them. For this reason, it is necessary to provide educational assistance in the form of scholarships and bring closer access to these scholarships for students, to support them to continue their education up to S1 and even S2 and S3. This was answered with the concept and design of the Scholarship Village, which was conceptualized as a scholarship information center; English language training support; and facilitation for students who are prospective scholarship recipients with scholarship providers or sources, by designing all their needs. These concepts and designs can be used as guidelines for the development of the Scholarship Village by the Government of North Sumatra.Keywords: Education, APK and APM, Scholarships, Concept and design